Research questions, methods and approach - Garrett, James; Bassett, Lucy; Levinson, F. James; Natalicchio, Marcela (International Food Policy Research Institute, 2011)
Drawing on the key issues illustrated by the framework (internal and external contexts, linking mechanisms, and dynamics) developed in Chapter 3, we have developed four primary sets of questions, following a rough chronology, to guide the empirical studies: • How do initiatives to work multisectorally get started? What are the triggers? • How does the collaboration work? How does it evolve over time? What are the dynamics and mechanisms of the collaboration process? • What are the issues surrounding the sustainability of collaboration? • What characterizes the broader environment in which the collaboration takes place? How does it affect the collaboration? Constructing a narrative around these questions should give us an idea of the key factors, or approaches, that affect how multisectoral collaboration comes about, how it operates, and how it might be sustained.